INSIDERS AND OUTSIDERS - Adams, Hazard (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1994)
This essay takes as its theme the humanistic principle of antithetical discourse as exemplified in the Irish literary tradition. In demonstrating the differences between external American views and internal Irish views of Irish writers, it traces the changing critical judgments of Yeats' and Joyce's respective places in the tradition.